Pandangan Masyarakat terhadap Makna yang Terkandung dalam Proses Antar Jujuran Suku Banjar - Khairunnisa; Lilik Andaryuni (CV. Creative Tugu Pena, 2024)
Marriage is a profound bond between a man and a woman aimed at forming a harmonious, loving, and compassionate family, grounded in the belief in the Almighty God. The Marriage Law No. 1 of 1974 governs marriage as a means to build a happy family, addressing both physical and spiritual needs. In practice, marriage involves the element of dowry or mahar, which varies by region. In Samarinda, the Banjar ethnic group has a tradition called